HAK IMUNITAS ADVOKAT BERDASARKAN UNDANG-UNDANG 18 TAHUN 2003 TENTANG ADVOKAT - Utama Ms, Robby Yunianto (Ensiklopedia of Journal, 2024)
The right to immunity or legal immunity is not only regulated in Article 16 of the Advocates Law concerning the immunity rights of an advocate but also in Article 50 of the Indonesian Criminal Code (KUHP). Additionally, the limitations on the right to immunity or legal immunity are outlined in Article 74 of the Criminal Procedure Code (KUHAP). In the handling of cases, the immunity rights of advocates apply both inside and outside the courtroom. The immunity is stipulated in Article 16 of the Advocates Law and reinforced by the Constitutional Court (MK) ruling. In this context, the immunity of advocates is always constrained by good faith, as defined in the Elucidation of Article 16 of the Advocates Law. Normatively, advocates have immunity that protects them from both civil and criminal liability when performing their professional duties for the defense of their clients, whether inside or outside the courtroom. However, this immunity is not absolute. The right to immunity or legal immunity also depends on the good faith of the advocate and is further regulated in Article 50 of the Criminal Code, which states, "Anyone who performs an act to implement the provisions of the law shall not be punished." However, this article includes legal exceptions.  Keywords: Rights, Immunity, Advocate.